Avaliação dos índices nacionais e regionais de preços recebidos pelos produtores agropecuários - Ostapechen, Leandra Aparecida Perego (2021)
Price indices measure the price fluctuation of different baskets of goods or services, and may be to the consumer or producer. The objective of this work was to calculate and analyze the Price Index Received by Rural Producers (IPR), with different baskets of products and regional aggregation. Specifically, the following indexes were calculated: IPR Regional Agriculture, IPR Regional Agricultural, IPR Regional Livestock, IPR Regionalized Agricultural, IPR Regional Agriculture 21 and IPR Local Regionalized Agriculture. The construction of these indices was preceded by the investigation of the representativeness of the IPR Brazil's price received by the producers of the Brazilian macro-regions, a central question of this work. On the one hand, the indices are constructed to reflect the price variation of products with greater participation in the financial volume of production, on the other hand, the products with lower participation in terms of financial volume tend not to be reflected in the price behavior of the national production. This scenario in Brazil has greater magnitudes due to the vast national territory. Therefore, national indexes reflect the economic dimension of few products, usually exporting such as soybeans, which are produced in virtually all national territory and regional products produced by an immense portion of producers are practically not reflected in the national indices Price data received by rural producers from January 2009 to May 2019 were used, assigned by CONAB (National Supply Company) and cointegration statistics to test the long-term relationship between the Brazilian and five Brazilian macro regions for each of the six calculated indices. The cointegration of the series was not confirmed in some regions of only two indices: southern region of the IPR Regional Livestock and; South, Southeast, Midwest and North regions of the IPR Local Regionalized Agriculture. The latter had a basket of products composed of products with lower economic participation in the production value of Brazil. This result suggests that prices in these regions are different from national prices according to the basket of products and that regional indices are important when showing regionally offered products. The indexes that resulted in co-integration of the regional series with the national series were composed of baskets of products that include different production scales and production value. The inclusion of products of greater representativeness in production value and products with lower participation in production value in the same index may have been the main factor that underscores the result of cointegration, that is, it causes regional indices to present the same price trend as the National index in the long term. It was concluded that products that are produced in only a few locations can have their prices tracked in regional indexes, while the National index is ideal for a view of the products with greater participation in the value of production as commodities.